Malaria in British military personnel deployed to Sierra Leone: a case series. Issue 1 (27th June 2016) - Quantick, Oliver; Howlett-Shipley, R; Roughton, S; Ross, D
Abstract : From December 2014 to April 2015, seven cases of malaria were seen in 1530 military personnel deployed to Sierra Leone on Operation GRITROCK in response to the West African Ebola outbreak, despite predeployment briefings, prescription of chemoprophylactic agents and bite prevention measures. The cases have prompted discussion regarding the efficacy of current measures and how to prevent future cases in deployed military personnel or more widely, those working in malaria-risk environments. All of the cases have made a full recovery and returned to work. We discuss what can be learnt concerning the choice of chemoprophylactic agent and whether anything further be added to standard operating procedures regarding bite prevention and treatment of cases.